Essential Oil Composition of the Different Parts and In Vitro Shoot Culture of Eryngium planum L - Thiem, Barbara (Molecules, 2011)
The essential oils obtained by hydrodistillation from the different parts (inflorescence, stalk leaves, rosette leaves and root) as well as from in vitro shoot culture of Eryngium planum L. were analyzed by GC-FID-MS in respect to their chemical composition. The different parts of E. planum and in vitro shoots showed different yields. The part with higher amount was the inflorescences, followed by the stalk leaves and in vitro shoots, rosette leaves and finally roots. The essential oils obtained from rosette leaves and in vitro-derived rosettes had totally different composition. Quantitative differences were also found between compounds of intact plant organs. The main components of stalk leaf oil and rosette leaf oil were monoterpene (limonene, α- and β-pinene) and sesquiterpene hydrocarbons. In inflorescence oil cis-chrysanthenyl acetate (43.2%) was accompanied by other esters (propionate, butanoate, hexanoate and octanoate) and numerous oxygenated sesquiterpenes. Root oil and in vitro shoot oil contained mainly (Z)-falcarinol and 2,3,4-trimethylbenzaldehyde. This is the first report on the chemical composition of this species.